The youth of social networks uses and the social networks for youth. A comparison between the uses of Facebook and HI5 among Romanian youth - Valentina Marinescu (Проблеми на постмодерността, 2011)
The present article analyses the "Self"-disclosure of the Romanian members of social network sites, namely Facebook and HI5. The initial assumption was that the users of social network sites perform certain daily activities (such as making friends) at the intersection of the online and offline lives. This is a result of the fact that through these socializing networks (Facebook si HI5) users can both create and erase the differences between the two interfaces (off- vs. on-) with the purpose of rendering a unitary image of the "Self" as members of a social network site. The purpose of the present study is to show the meanings that the users attribute to the experiences of their online activity on the social network sites, preferring a qualitative approach of the studied issue. On the basis of the information provided by a specific age group - teenagers and young people - we can say that our results points to the fact that for the young Romanian users of social network sites (e.g. Facebook si HI5) the answer to the question: "Why should I register on a social network?" could be summed up the following way: "I register on a social network site because all my friends already have an account there". In other words, like in the case of young people and teenagers from other countries, and as the specialty literature shows the idea of belonging as a member to a social network site is associated to the desire of integrating and being accepted in a group as equal (in age and preoccupations), to the desire of not losing contact with friends, to the appropriate medium for setting up a new friendship and at the same time, relaxing, and having a great free time.